Molecular Mechanisms of Glucocorticoid Resistance in Corticotropinomas: New Developments and Drug Targets - Ciato, Denis; Albani, Adriana (Frontiers in Endocrinology, 2020)
Cushing´s disease is characterized by excessive adrenocorticotropin hormone (ACTH) secretion caused by a corticotroph tumour of the pituitary gland, leading to hypercortisolism and increased morbidity and mortality. The molecular causes of the disease are not completely understood, therefore more research is needed to discover novel molecular targets and more effective treatments. To date, the SSTR-analogue pasireotide is the only approved drug for Cushing´s Disease treatment that is directly targeting the source of the disease. Targeting directly the activity of glucocorticoid receptor or the factors modulating it might be a new valid option for the medical management of Cushing´s disease. Here, we briefly review the molecular mechanisms involved in the glucocorticoid negative feedback and glucocorticoid resistance and examine novel targets and therapies that might effectively restore glucocorticoid sensitivity.